THE SYSTEM PARADIGM AS THE RESEARCH METHODOLOGY OF THE CREDIT MARKET - N. E. Brovkina (Финансы: теория и практика)
Introduction. The importance of facing the country’s strategic objectives makes it necessary to make more active use of the entire spectrum of credit and financial relations, in particular, leads to the enhancement of the role of the credit market, which currently present a number of challenges. Despite the fact that the term “credit market” is widely used by practitioners and economists, the theoretical foundations, revealing the contents of the credit market in the scientific literature insufficiently developed. Moreover, economists differ in defining its content and constituent elements. There is a need for a theoretical study of the credit market as an integrated system, provide the basis for the search of practical solutions.Purpose. To investigate the Russian credit market as a developing social-economic system, relatively isolated in space and relatively stable in time, which has both the properties of external integrity and internal variety. To determine the driving force of its development.Methods. A study of the credit market as an integrated system was based on the system paradigm, proposed by J. Kornai and comprehensively developed by G. B. Kleiner.Results. The use of a system paradigm allowed to investigate the credit market as an integrated system, to define process system as dominant and to formulate its mission, which is providing constant modernization of the means and opportunities for effective interaction of market participants by balancing the demand for credit products and supply, increases the capacity of the credit market, its proportionality, and promoting competition. The system approach allowed also to prove that the credit market develops under the influence of internal forces, and under the influence of dynamically changing environment, and appropriate management decisions.Prospects. The results of theoretical research of the credit market on the basis of methodological approaches determined by the system paradigm can form the direction of its comprehensive modernization, including the modernization of regulation of the credit market, creating market institutions and socio-economic development of the country. Conclusions. A study of the credit market as a developing integrated socio-economic system, identified process system as the main driving force of its development and also to disclose the significant influence of the environment and the regulatory system on the credit market. Thus the purpose of the article was achieved.